CONSTITUENTS OF ESSENTIAL OILS FROM LEAVES AND SEEDS OF LAURUS NOBILIS L.: A CHEMOTAXONOMIC APPROACH - Elkiran, Omer; Akbaba, Emel; Bagci, Eyup (Bangladesh Botanical Soc, 2018)
In the present study, chemical compositions of essential oils from seeds and leaves of laurel (Laurus nobilis L.) were evaluated using GC-GC/MS system. Sixty nine different compounds were identified constituting 86.7% of the total oil from the seed, while 76 compounds were determined, constituting 95.8% of the total oil extracted from the leaves. The major compounds of essential oil from laurel seeds included eucalyptol (17.2%), alpha-terpinyl acetate (9.0%), caryophyllene oxide (6.1%), spathulenol (5.0%) and methyl eugenol (4.2%), constituting 41.5% of the total oil. However, eucalyptol (18.0%), alpha-terpinyl acetate (13.1%), sabinene (7.8%), alpha-pinene (4.5%), 2 (4-methoxyphenyl)-N,N,2-trimethyl-1-pyrroline (4.4%) were identified as the major compounds in the oil from laurel leaves, constituting 47.8% of the total oil. Eucalyptol and aterpinyl acetate, belonging to monoterpenoids, were determined in the highest concentrations within both oils. However, the other principle compounds differ between the two volatile oils.
Keywords: Laurus nobilis; Essential oil; Eucalyptol; alpha-terpinyl acetate